The different trends in the burden of neurological and mental disorders following dietary transition in China, the USA, and the world: An extension analysis for the Global Burden of Disease Study 2019 - Liang, Shan; Wang, Li; Wu, Xiaoli; Hu, Xu; Wang, Tao; Jin, Feng (Frontiers in Nutrition, 2023)
Introduction The highly processed western diet is substituting the low-processed traditional diet in the last decades globally. Increasing research found that a diet with poor quality such as western diet disrupts gut microbiota and increases the susceptibility to various neurological and mental disorders, while a balanced diet regulates gut microbiota and prevents and alleviates the neurological and mental disorders. Yet, there is limited research on the association between the disease burden expanding of neurological and mental disorders with a dietary transition. Methods We compared the disability-adjusted life-years (DALYs) trend by age for neurological and mental disorders in China, in the United States of America (USA), and across the world from 1990 to 2019, evaluated the dietary transition in the past 60 years, and analyzed the association between the burden trend of the two disorders with the changes in diet composition and food production. Results We identified an age-related upward pattern in disease burden in China. Compared with the USA and the world, the Chinese neurological and mental disorders DALY percent was least in the generation over 75 but rapidly increased in younger generations and surpassed the USA and/or the world in the last decades. The age-related upward pattern in Chinese disease burdens had not only shown in the presence of cardiovascular diseases, neoplasms, and diabetes mellitus but also appeared in the presence of depressive disorders, Parkinson’s disease, Alzheimer’s disease and other dementias, schizophrenia, headache disorders, anxiety disorders, conduct disorders, autism spectrum disorders, and eating disorders, successively. Additionally, the upward trend was associated with the dramatic dietary transition including a reduction in dietary quality and food production sustainability, during which the younger generation is more affected than the older. Following the increase in total calorie intake, alcohol intake, ratios of animal to vegetal foods, and poultry meat to pulses, the burdens of the above diseases continuously rose. Then, following the rise of the ratios of meat to pulses, eggs to pulses, and pork to pulses, the usage of fertilizers, the farming density of pigs, and the burdens of the above disease except diabetes mellitus were also ever-increasing. Even the usage of pesticides was positively correlated with the burdens of Parkinson’s disease, schizophrenia, cardiovascular diseases, and neoplasms. Contrary to China, the corresponding burdens of the USA trended to reduce with the improvements in diet quality and food production sustainability. Discussion Our results suggest that improving diet quality and food production sustainability might be a promising way to stop the expanding burdens of neurological and mental disorders.